Anti-cracking 3D printing concrete and preparation method thereof
By optimizing the material formula of 3D printing concrete, the surface cracks and penetration problems caused by excessive water increases are solved, and the high strength, durability and construction performance of the structure are realized.
Patent Information
- Application Number
- CN202411522024.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
AI Technical Summary
Surface cracks and penetration problems caused by excessive water addition in 3D printed concrete affect the durability and safety of the structure.
By adjusting the formula of the material, including cement, steel residue, mineral powder, powder coal ash, furnace bottom scum collection, mask, silica ash, composite fracture agent, composite fiber, sodium silicate, active agent and citric acid, optimize Water control, reduce cracks, and enhance structural strength and stability.
A significant reduction of 3D printing concrete water increase, improvement of construction performance and final structural strength, reducing the generation of surface cracks, and improving the overall quality and long -term durability of the structure.
Smart Images

Figure BDA0005108264140000111 
Figure BDA0005108264140000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of concrete, and in particular to anti-cracking 3D printing concrete and a preparation method thereof. Background Art
[0002] With the rapid development and technological innovation of the construction industry, 3D printing technology, as a revolutionary manufacturing method, is gradually penetrating and changing the face of traditional construction. Especially in the construction of concrete structures, 3D printing concrete technology, with its advantages of high efficiency, flexibility, and precise molding, provides unprecedented possibilities for the design and realization of complex structures. However, this cutting-edge technology also faces many challenges in its actual application. Among them, the surface cracks caused by improper control of water addition and the subsequent penetration and cracking problems are particularly prominent, becoming one of the key bottlenecks restricting the large-scale commercial application of 3D printing concrete technology.
[0003] In the traditional concrete pouring process, the water-cement ratio (i.e., the mass ratio of water to cement) is an important factor in determining the performance and ultimate strength of concrete. An appropriate water-cement ratio can ensure that the concrete has good fluidity and plasticity, facilitate construction operations, and ensure that the hardened concrete meets the mechanical properties required by the design. However, in 3D printing concrete technology, due to the special requirements of the printing process on the rheological properties of the material, it is often necessary to increase the water content to improve the fluidity of the concrete and ensure that the material can be smoothly extruded through the nozzle to form a precise stacked structure. Although this high water content is conducive to the implementation of the printing process, it also poses a hidden danger to the later performance of the structure.
[0004] Too much water addition will directly lead to excess free water in the concrete solidification process. These free water will form capillary pores in the concrete during evaporation, reducing the density of the concrete, thus forming tiny cracks on the surface or inside. Surface cracks not only affect the beauty of the building, but more importantly, reduce the impermeability and durability of the concrete, making the structure susceptible to environmental erosion, such as water penetration, salt corrosion, etc. In the long run, it will seriously threaten the safe use and life of the building.
[0005] Therefore, solving the surface cracks and penetration problems caused by excessive water addition in 3D printed concrete is of great significance for promoting the mature application of this technology and expanding its potential in the field of construction. This requires researchers to not only deeply explore the material science basis of 3D printed concrete and optimize the concrete mix ratio, but also innovate the printing process, introduce intelligent control technology, and accurately control the evaporation and solidification rate of water during the printing process, so as to fundamentally improve the microstructure and macroscopic properties of concrete. Summary of the invention
[0006] In view of the shortcomings of the prior art mentioned above, the purpose of the present invention is to provide a crack-resistant 3D printed concrete and a preparation method, which can effectively reduce excess moisture in the concrete, prevent the formation of surface cracks, and improve the overall quality and long-term durability of the printed structure by innovatively adjusting the material formula.
[0007] In order to achieve the above-mentioned object and other related objects, the present invention provides an anti-cracking 3D printing concrete, which comprises the following raw material components by mass percentage:
[0008] Cement 28-32%, 2-4mm steel slag 6-8%, 0-2mm steel slag 36-39%, mineral powder 7-10%, secondary fly ash 6-8%, bottom slag fine aggregate 5-7%, montmorillonite 2-3%, silica fume 0.5-1%, composite anti-cracking agent 0.5-1%, composite fiber 0.03-0.06%, sodium silicate 0.5-1%, activator 0.04-0.06%, citric acid 0.03-0.05%.
[0009] Preferably, the anti-cracking 3D printing concrete of the present invention includes the following raw material components, by mass percentage: 30% cement, 7% 2-4mm steel slag, 37% 0-2mm steel slag, 8% mineral powder, 7% secondary fly ash, 6% bottom slag fine aggregate, 2.5% montmorillonite, 0.8% silica fume, 0.86% composite anti-cracking agent, 0.05% composite fiber, 0.7% sodium silicate, 0.05% active agent, and 0.04% citric acid.
[0010] Preferably, the cement is SAC 42.5 grade.
[0011] Preferably, the fCaO content in the 2-4 mm steel slag is less than 3%.
[0012] Preferably, the CaO content in the 0-2 mm steel slag is less than 3%.
[0013] Preferably, the particle size of the secondary fly ash is 325 mesh.
[0014] Preferably, the bottom slag fine aggregate has a particle size of 0-2 mm.
[0015] Preferably, the SiO in the silica ash 2 ≥92%.
[0016] Preferably, the sodium silicate and citric acid are both of industrial grade.
[0017] Preferably, the montmorillonite contains A 2 O 3 ≥46%、SiO 2 ≥52%, and the particle size of the montmorillonite is 1250 mesh.
[0018] Preferably, the active agent is FS-65 type water reducing agent.
[0019] Preferably, the composite anti-cracking agent has the following raw material components in percentage by weight: CaSO 4 The whiskers are 20-30% and the light calcium carbonate is 70-80%.
[0020] Preferably, the raw material components of the composite fiber are as follows: 60-70% by weight of chopped glass fiber and 30-40% by weight of low-melting-point organic fiber.
[0021] Preferably, the mass percentage of 0-2 mm steel slag + bottom slag fine aggregate in the 3D printing concrete is 42-45%; the mass percentage of cement + mineral powder is 36.5-39.5%.
[0022] Preferably, the mass percentage of the active agent + citric acid in the 3D printing concrete is 0.08-0.1%.
[0023] The present invention also provides a method for preparing the anti-cracking 3D printed concrete as described above, comprising the following steps:
[0024] S1. Premixing the composite anti-cracking agent, composite fiber, sodium silicate, active agent and citric acid to obtain a premixed small material;
[0025] S2. Mix cement, 2-4 mm steel slag, 0-2 mm steel slag, mineral powder, secondary fly ash, bottom slag fine aggregate, montmorillonite, silica fume and water, add premixed small materials and continue to mix and stir evenly to obtain anti-cracking 3D printing concrete.
[0026] As described above, the anti-cracking 3D printed concrete and preparation method of the present invention have the following beneficial effects:
[0027] 1. The anti-cracking 3D printing concrete of the present invention uses cement, 2-4mm steel slag, 0-2mm steel slag, mineral powder, secondary fly ash, bottom slag fine aggregate, montmorillonite, silica fume, composite anti-cracking agent, composite fiber, sodium silicate, active agent and citric acid as raw materials. The addition of multifunctional composite additives such as composite anti-cracking agent and composite fiber not only significantly reduces the amount of water required for 3D printing concrete, but also greatly improves its construction performance and final structural strength, achieving an innovative breakthrough in traditional 3D printing concrete technology.
[0028] 2. The anti-cracking 3D printed concrete of the present invention effectively reduces the dependence of the concrete system on excess water through a carefully designed raw material ratio, can significantly improve the density of the concrete, reduce internal pores, and thus reduce shrinkage cracks caused by water evaporation. The addition of additives such as composite anti-cracking agents and improvements through chemical and physical effects enhance the toughness and crack resistance of the concrete and prevent the generation of surface cracks.
[0029] 3. The use of steel slag and bottom slag fine aggregates in the anti-cracking 3D printed concrete of the present invention not only replaces part of the traditional aggregates and reduces resource consumption, but also increases the wear resistance and long-term stability of the concrete; the recycling of these industrial wastes is both environmentally friendly and economical. At the same time, its unique particle morphology helps to improve the compressive and tensile strength of the concrete.
[0030] 4. The addition of mineral powder, secondary fly ash and montmorillonite in the anti-cracking 3D printing concrete of the present invention improves the fluidity and plasticity of the concrete, making it easier for the concrete to pass through the nozzle during the printing process, and maintains good interlayer bonding when constructing complex shapes, reducing blockage during the printing process.
[0031] 5. The addition of composite fibers to the anti-cracking 3D printed concrete of the present invention enhances the crack resistance and toughness of the concrete, especially for resisting cracking caused by long-term loads and environmental factors; the use of active agents and citric acid promotes the hydration reaction of cement-based materials and improves the overall durability of concrete. In addition, the formula also has good anti-penetration performance, reduces the penetration of moisture and harmful substances, prevents surface cracks, improves the overall quality and long-term durability of the printed structure, extends the service life of the structure, and absorbs solid waste. DETAILED DESCRIPTION
[0032] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0033] When a numerical range is disclosed herein, the above range is deemed to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all sub-ranges included therein. For example, a specified range from "1 to 10" should be deemed to include any and all sub-ranges between a minimum of 1 and a maximum of 10. Exemplary sub-ranges of ranges 1 to 10 include, but are not limited to, 1 to 6.1, 3.5 to 7.8, 5.5 to 10, and the like.
[0034] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; and, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0035] The first aspect of the present invention provides an anti-cracking 3D printing concrete, which includes the following raw material components by mass percentage:
[0036] Cement 28-32%, 28-29%, 29-30%, 30-31% or 31-32%, 2-4mm steel slag 6-8%, 6-7% or 7-8%, 0-2mm steel slag 36-39%, 36-37%, 37-38% or 38-39%, mineral powder 7-10%, 7-8%, 8-9% or 9-10%, secondary fly ash 6-8%, 6-7% or 7-8%, bottom slag fine aggregate 5-7%, 5-6% or 6-7%, montmorillonite 2-3%, 2-2.5% or 2.5-3%, silica fume 0.5-1%, 0.5-0.7%, 0.7-0 .9% or 0.9-1%, composite anti-cracking agent 0.5-1%, 0.5-0.7%, 0.7-0.9% or 0.9-1%, composite fiber 0.03-0.06%, 0.03-0.04%, 0.04-0.05% or 0.05-0.06%, sodium silicate 0.5-1%, 0.5-0.7%, 0.7-0.9% or 0.9-1%, activator 0.04-0.06%, 0.04-0.05% or 0.05-0.06%, citric acid 0.03-0.05%, 0.03-0.04% or 0.04-0.05%.
[0037] In a preferred embodiment of the present invention, the anti-cracking 3D printing concrete includes the following raw material components by mass percentage:
[0038] Cement 30%, 2-4mm steel slag 7%, 0-2mm steel slag 37%, mineral powder 8%, secondary fly ash 7%, bottom slag fine aggregate 6%, montmorillonite 2.5%, silica fume 0.8%, composite anti-cracking agent 0.86%, composite fiber 0.05%, sodium silicate 0.7%, activator 0.05%, citric acid 0.04%.
[0039] In some embodiments of the present invention, the cement is SAC 42.5 grade.
[0040] In some embodiments of the present invention, the f CaO content in the 2-4 mm steel slag is less than 3%, for example, less than 1%, 1-2%, or 2-3%.
[0041] In some embodiments of the present invention, the f CaO content in the 0-2 mm steel slag is less than 3%, for example, less than 1%, 1-2%, or 2-3%.
[0042] In some embodiments of the present invention, the mineral powder is of S95 grade.
[0043] In some embodiments of the present invention, the particle size of the secondary fly ash is 325 mesh.
[0044] In some embodiments of the present invention, the bottom slag fine aggregate has a particle size of 0 to 2 mm, for example, 1 to 0.5 mm, 0.5 to 1 mm, 1 to 1.5 mm or 1.5 to 2 mm.
[0045] In some embodiments of the present invention, the SiO 2 ≥92%. For example, 92-94%, 94-96%, 96-98%, or ≥98%.
[0046] In some embodiments of the present invention, the sodium silicate is industrial grade. The addition of silica fume and sodium silicate in the present invention is mainly to improve the performance of concrete, including strength, durability and printability. Its effects and functions are as follows: (1) Silica fume plays a role in microscopic filling and strengthening of concrete, accelerating hydration reaction and improving durability. Silica fume has a high specific surface area. Silica fume can fill the micropores in the cement paste, reduce porosity, and improve the density and strength of concrete. This microscopic filling effect helps to enhance the structural integrity of 3D printed concrete and reduce the risk of cracking. Silica fume can also react with cement hydration products to generate additional hydrated calcium silicate gel, accelerate the hydration process of cement, and promote the development of early strength, which is particularly important for 3D printed concrete that requires rapid prototyping. The addition of silica fume can also improve the concrete's impermeability, chemical corrosion resistance and freeze-thaw cycle resistance, and extend the service life of 3D printed structures, especially in harsh and cold natural environments. (2) Sodium silicate can reduce the water content of concrete, improve its rheological properties, enhance its workability and stability, and improve its strength and durability. As a high-efficiency water reducer, sodium silicate can significantly reduce the water demand of concrete while maintaining or improving its fluidity and pumpability, helping to improve the fluidity of the mixture and the smoothness of the nozzle, reducing the risk of blockage during printing. Sodium silicate can also adjust the setting time of concrete, providing a longer working time while maintaining the stability of the mixture, which is very beneficial for 3D printing processes that require precise control of material flow and shape retention. In addition, sodium silicate can promote the formation of cement hydration products and enhance the internal structure of the cement matrix, thereby improving the early and late strength of concrete. At the same time, it can also improve the microstructure of concrete and enhance its durability, such as improving impermeability and reducing chloride ion penetration.
[0047] In some embodiments of the present invention, the citric acid is industrial grade. In the present invention, citric acid acts as a retarder to enhance the construction performance of concrete. Its effects and functions are as follows: (1) pH adjustment and construction performance maintenance: Citric acid, as a weak acid, can adjust the pH value of the concrete mixture, create a more stable alkaline environment, help control the speed and efficiency of cement hydration reaction, prevent excessive solidification from affecting the continuity of the printing process, and also reduce the matrix instability problem caused by pH fluctuations, thereby improving the homogeneity and reliability of printed concrete. (2) Metal ion chelation: Concrete raw materials contain trace amounts of metal ions (such as calcium, magnesium, etc.), which may affect the hydration process of cement or react with additives, resulting in a decrease in concrete performance. Citric acid can form stable chelates with these metal ions to reduce their harmful effects, such as reducing the viscosity of cement paste and improving fluidity, which is particularly important for 3D printing concrete mixtures that require good fluidity and printability. (3) Improve construction performance and reduce cracks: By adjusting the chemical balance and physical properties of the concrete mixture, citric acid helps improve the rheology of concrete, making it more suitable for the requirements of 3D printing technology. Good workability can reduce the resistance during the printing process, allowing the material to be extruded more smoothly, helping to reduce the generation of cracks between printed layers and improving the overall quality and appearance of the printed structure. (4) Promoting the control of the curing process: The addition of citric acid participates in the formation of cement hydration products, affecting the growth pattern of crystals, thereby regulating the curing speed and microstructure of concrete, which is beneficial for the rapid prototyping and later strength formation of 3D printed concrete. The introduction of citric acid in the present invention is beneficial to improving the workability of concrete, controlling the hydration process, reducing crack generation and improving the performance and stability of the final product.
[0048] In some embodiments of the present invention, the montmorillonite contains A 2 O 3 ≥46%、SiO 2≥52%, the particle size of the montmorillonite is 1250 mesh. The purpose of adding montmorillonite in the present invention is to improve the workability of concrete, enhance the strength of concrete after drying, reduce drying shrinkage and printing strength reduction rate, and the specific effects are as follows: (1) Enhance structure and stability: The nano-scale particles of montmorillonite can be filled into the pores of the cement matrix to form a more compact structure, thereby improving the early strength and long-term durability of 3D printed concrete. This nano-scale enhancement is beneficial to the stability of the printed parts during the construction process and the integrity of the structure after printing. (2) Improve rheology: By adjusting the content of montmorillonite, the rheology (i.e. plasticity and viscosity) of the concrete mixture can be optimized, which is crucial for 3D printing. Good rheological properties ensure that the mixture can be extruded smoothly during the printing process, while maintaining a stable shape, reducing interlayer cracking, and improving printing accuracy. (3) Slow down and reduce evaporation: Montmorillonite has a certain water absorption and expansion property, which can slow down water evaporation to a certain extent. This is particularly beneficial for 3D printing processes that require a long printing time. Maintaining appropriate humidity helps control the curing rate of concrete and avoid cracks caused by premature drying. (4) Improving interfacial interactions: In the 3D printing process, the bonding strength between layers is the key to ensuring the stability of the overall structure. The addition of montmorillonite can improve the bonding between cement paste and aggregate or the previous layer of concrete, enhance interlayer bonding, and reduce interface defects. (5) Adjusting the printable window: The addition of montmorillonite can also affect the effectiveness of concrete admixtures (such as water reducers), indirectly affecting the dispersibility of concrete through competitive adsorption mechanisms or adjusting the charge distribution of the paste, helping to find a wider printable window and making the printing process more controllable.
[0049] In some embodiments of the present invention, the active agent is a FS-65 water reducer. The active agent introduced in the present invention is a FS-65 water reducer, which is based on its function as a high-performance water reducer or rheology modifier. Its effects and functions are as follows: (1) Increase fluidity: The active agent FS-65 can significantly reduce the friction between cement particles, so that under the same water-cement ratio, the fluidity of the concrete mixture is greatly improved. This is particularly important for 3D printing, because higher fluidity helps concrete to pass through the printing nozzle better and form fine and complex structures, while reducing interlayer gaps and improving printing accuracy. (2) Reduce water consumption: Through efficient dispersion, the active agent FS-65 can reduce the amount of water used in concrete while maintaining the required workability. Reducing water consumption not only helps control the shrinkage of concrete and prevent cracks, but also improves the early and late strength of concrete and enhances durability. (3) Optimize microstructure: The addition of active agent can promote a more uniform distribution of hydration products in the cement hydration process and form a denser microstructure, which helps to improve the concrete's impermeability and chemical corrosion resistance, which is particularly important for the long-term performance of 3D printed concrete. (4) Improve construction performance: During the 3D printing process, the use of active agent FS-65 can also improve the material's retention, that is, the stability of concrete in a static state, prevent material stratification or precipitation during the printing process, and ensure the smooth progress of continuous printing operations. The active agent in the present invention significantly improves the construction performance, mechanical properties and durability of concrete through its unique dispersing, water-reducing and structural regulation effects, and is one of the effective methods to solve a series of problems caused by high water addition in 3D printed concrete.
[0050] In some embodiments of the present invention, the composite anti-cracking agent has the following raw material components by mass percentage: CaSO 4 The whisker is 20-30%, 20-25% or 25-30%, and the light calcium carbonate is 70-80%, 70-75% or 75-80%.
[0051] The present invention adopts CaSO 4 Whiskers and light calcium carbonate are introduced as composite anti-cracking agents. They play unique roles in the application of 3D printing concrete and improve the performance of concrete through different mechanisms. Their roles and functions are as follows: (1) CaSO 4 Whiskers can enhance the mechanical properties of concrete, improve the microstructure of concrete, and regulate the hydration process. 4 Whiskers have a high aspect ratio and, like micro-rebars, can effectively hinder the expansion of micro-cracks inside concrete and improve the overall tensile strength, bending strength and toughness of the material. This "bridging effect" reduces stress concentration at the crack tip and increases the fracture energy of concrete. 4The uniform distribution of whiskers in the concrete matrix can optimize the microstructure, reduce porosity, and improve the density and durability of the material, including impermeability and chemical corrosion resistance. 4 Whiskers may also participate in the cement hydration process to form denser hydration products, further strengthen the interfacial bonding force, and help improve the overall performance of concrete. (2) Light calcium carbonate has a water-reducing effect in 3D printed concrete and fills in micro-pores, and can improve the construction performance of concrete and enhance the later strength of concrete. Although the direct water-reducing effect of light calcium carbonate is not as good as that of professional water-reducing agents, the addition of light calcium carbonate can improve the rheological properties of concrete paste, reduce water consumption through physical filling effects, thereby improving the consistency and stability of concrete, and facilitating precise molding during 3D printing. Its fine particles can fill the pores in the cement paste, reduce porosity, improve the density and surface finish of concrete, and help reduce the generation of surface cracks. The presence of calcium carbonate particles helps to adjust the rheological properties of the paste, so that the concrete has better fluidity and retention during printing, ensuring the accurate construction of complex shapes, while reducing interlayer separation during printing. In addition, the secondary hydration reaction of light calcium carbonate during the cement hydration process can promote the crystallization and bonding of the cement matrix, which helps to improve the compressive and flexural strength of concrete in the long run. 4 The synergistic effect of whiskers and lightweight calcium carbonate jointly improves the construction performance, mechanical properties and durability of 3D printed concrete.
[0052] In some embodiments of the present invention, the raw material components of the composite fiber are as follows: 60-70%, 60-65% or 65-70% of chopped glass fiber, and 30-40%, 30-35% or 35-40% of low melting point organic fiber.
[0053] The present invention introduces short-cut glass fibers and low-melting-point organic fibers as composite fibers, mainly to enhance the mechanical properties, crack resistance and durability of concrete. Its effects and functions are as follows: (1) Short-cut glass fibers play a role in strengthening, crack resistance and seepage prevention, and stabilizing the printing process. Short-cut glass fibers have high strength and high elastic modulus. When evenly distributed in the concrete matrix, they can form a large number of microscopic "reinforcement bars", effectively improving the tensile strength, bending strength and toughness of concrete. The bridging effect of the fibers can absorb energy when cracks inside the concrete are initiated and developed, preventing the further expansion of the cracks. Due to the addition of short-cut glass fibers, the crack width of the concrete is effectively controlled, the penetration path of water and other harmful media is reduced, and the impermeability and corrosion resistance of the concrete are enhanced, which is crucial for extending the service life of 3D printed concrete structures. At the same time, short-cut fibers can also improve the rheological properties of concrete mixtures, help adjust the fluidity and conformality of printed materials, ensure that the materials can be uniformly extruded during the 3D printing process, and maintain good bonding and stability when stacked layer by layer. (2) Low-melting-point organic fibers improve the temperature adaptability, plasticity and construction convenience of concrete. Low-melting-point organic fibers can soften or even partially melt when stirred, which is particularly important in the 3D printing process. In the post-printing stage, the melting of organic fibers can fill the micropores inside the concrete to form a tighter structure, while also promoting the bonding between different printed layers and enhancing the integrity of the overall structure. The addition of organic fibers can also improve the plastic deformation capacity of concrete, especially in high or low temperature environments, helping to alleviate stress concentration caused by temperature differences and reduce the generation of cracks. This plastic enhancement is particularly beneficial for 3D printed structures that are subjected to complex stress states. It can also effectively improve the construction performance of concrete mixtures, such as improving its pumpability and interlayer bonding during printing, making the printing process smoother and the surface quality of the structure higher. The present invention utilizes the respective strengthening, crack prevention and modification effects of short-cut glass fibers and low-melting-point organic fibers to synergistically improve the comprehensive performance of 3D printed concrete, solve the surface cracks and penetration problems caused by the large amount of traditional water addition, and provide an important material basis for the widespread application of 3D printing technology in the field of construction.
[0054] In some embodiments of the present invention, the mass percentage of 0-2 mm steel slag + bottom slag fine aggregate in the 3D printed concrete is 42-45%, 42-43%, 43-44% or 44-45%; the mass percentage of cement + mineral powder is 36.5-39.5%, 36.5-37%, 37-37.5%, 37.5-38%, 38-38.5%, 38.5-39% or 39-39.5%.
[0055] In some embodiments of the present invention, the mass percentage of the active agent + citric acid in the 3D printing concrete is 0.08-0.1%, for example, 0.08-0.09% or 0.09-0.1%.
[0056] A second aspect of the present invention provides a method for preparing the anti-cracking 3D printed concrete as described above, comprising the following steps:
[0057] S1. Premix the composite anti-cracking agent, composite fiber, sodium silicate, active agent and citric acid to obtain a premixed small material; after premixing, pack it in a moisture-proof manner and add it when mixing materials at the construction site;
[0058] S2. Mix cement, 2-4 mm steel slag, 0-2 mm steel slag, mineral powder, secondary fly ash, bottom slag fine aggregate, montmorillonite, silica fume and water, add premixed small materials and continue to mix and stir evenly to obtain anti-cracking 3D printing concrete.
[0059] The amount of water added is 7-14% relative to the total amount of 3D printing concrete raw materials (ie, water addition rate).
[0060] Example 1
[0061] A crack-proof 3D printing concrete includes the following raw material components, measured by mass percentage: 30% cement, 7% 2-4mm steel slag, 37% 0-2mm steel slag, 8% mineral powder, 7% secondary fly ash, 6% bottom slag fine aggregate, 2.5% montmorillonite, 0.8% silica fume, 0.86% composite anti-cracking agent, 0.05% composite fiber, 0.7% sodium silicate, 0.05% active agent, and 0.04% citric acid.
[0062] The method for preparing the above-mentioned anti-cracking 3D printed concrete comprises the following steps:
[0063] S1. Premixing the composite anti-cracking agent, composite fiber, sodium silicate, active agent and citric acid to obtain a premixed small material;
[0064] S2. Mix cement, 2-4 mm steel slag, 0-2 mm steel slag, mineral powder, secondary fly ash, bottom slag fine aggregate, montmorillonite, silica fume and water, add premixed small materials and continue to mix and stir evenly to obtain anti-cracking 3D printing concrete.
[0065] Example 2
[0066] A crack-proof 3D printing concrete includes the following raw material components, measured by mass percentage: 28% cement, 6.6% 2-4mm steel slag, 36% 0-2mm steel slag, 9.3% mineral powder, 8% secondary fly ash, 6.7% bottom slag fine aggregate, 2.8% montmorillonite, 1% silica fume, 0.67% composite anti-cracking agent, 0.04% composite fiber, 0.8% sodium silicate, 0.06% active agent, and 0.03% citric acid.
[0067] The preparation method of the above-mentioned anti-cracking 3D printed concrete is the same as that in Example 1.
[0068] Example 3
[0069] A crack-proof 3D printing concrete includes the following raw material components, measured by mass percentage: 30.7% cement, 6.8% 2-4mm steel slag, 39% 0-2mm steel slag, 7.6% mineral powder, 6% secondary fly ash, 5.2% bottom slag fine aggregate, 2% montmorillonite, 0.6% silica fume, 0.94% composite anti-cracking agent, 0.06% composite fiber, 1% sodium silicate, 0.05% active agent, and 0.05% citric acid.
[0070] The preparation method of the above-mentioned anti-cracking 3D printed concrete is the same as that in Example 1.
[0071] Example 4
[0072] A crack-proof 3D printing concrete includes the following raw material components, measured by mass percentage: 29% cement, 6.2% 2-4mm steel slag, 37.6% 0-2mm steel slag, 10% mineral powder, 6.5% secondary fly ash, 5.8% bottom slag fine aggregate, 3% montmorillonite, 0.7% silica fume, 0.5% composite anti-cracking agent, 0.05% composite fiber, 0.57% sodium silicate, 0.04% active agent, and 0.04% citric acid.
[0073] The preparation method of the above-mentioned anti-cracking 3D printed concrete is the same as that in Example 1.
[0074] Example 5
[0075] A crack-proof 3D printing concrete includes the following raw material components, measured by mass percentage: 32% cement, 8% 2-4mm steel slag, 37.9% 0-2mm steel slag, 7% mineral powder, 6.2% secondary fly ash, 5% bottom slag fine aggregate, 2.2% montmorillonite, 0.5% silica fume, 0.57% composite anti-cracking agent, 0.03% composite fiber, 0.5% sodium silicate, 0.05% active agent, and 0.05% citric acid.
[0076] The preparation method of the above-mentioned anti-cracking 3D printed concrete is the same as that in Example 1.
[0077] Example 6
[0078] A crack-proof 3D printing concrete includes the following raw material components, measured by mass percentage: 28.3% cement, 6% 2-4mm steel slag, 37.5% 0-2mm steel slag, 8.3% mineral powder, 7.6% secondary fly ash, 7% bottom slag fine aggregate, 2.5% montmorillonite, 0.77% silica fume, 1% composite anti-cracking agent, 0.04% composite fiber, 0.9% sodium silicate, 0.06% active agent, and 0.03% citric acid.
[0079] The preparation method of the above-mentioned anti-cracking 3D printed concrete is the same as that in Example 1.
[0080] Comparative Example 1
[0081] Compared with Example 2, Comparative Example 1 does not contain montmorillonite, the amount of cement is increased accordingly, and the remaining raw material compositions and preparation steps are exactly the same as those of Example 2.
[0082] Comparative Example 2
[0083] Compared with Example 3, Comparative Example 2 does not contain a composite anti-cracking agent, the amount of cement is increased accordingly, and the remaining raw material compositions and preparation steps are exactly the same as those of Example 3.
[0084] Comparative Example 3
[0085] Compared with Example 4, Comparative Example 3 does not contain composite fibers, the amount of cement is increased accordingly, and the remaining raw material compositions and preparation steps are exactly the same as those of Example 4.
[0086] Comparative Example 4
[0087] Compared with Example 5, Comparative Example 4 does not contain an active agent, the amount of mineral powder is increased accordingly, and the remaining raw material composition and preparation steps are exactly the same as those of Example 5.
[0088] Comparative Example 5
[0089] Compared with Example 6, Comparative Example 5 does not contain citric acid, the amount of cement is increased accordingly, and the remaining raw material compositions and preparation steps are exactly the same as those of Example 6.
[0090] The specific contents of each raw material component of Examples 1 to 6 and Comparative Examples 1 to 5 are shown in Table 1.
[0091] Table 1 Raw material composition of Examples 1 to 6 and Comparative Examples 1 to 5, wt%
[0092]
[0093] Performance Testing:
[0094] The anti-cracking 3D printed concrete of Examples 1 to 6 and Comparative Examples 1 to 5 was tested for fluidity, setting time, extrudability, support, printing strength reduction rate, and interlaminar splitting strength in accordance with the provisions of TCECS 786-2020 Technical Specification for Concrete 3D Printing. The surface microcracks were visually inspected on the surface of the printed body after natural drying. The material properties of the anti-cracking 3D printed concrete of Examples 1 to 6 and Comparative Examples 1 to 5 are shown in Table 2.
[0095] Table 2 Test results of Examples 1 to 6 and Comparative Examples 1 to 5
[0096]
[0097]
[0098] The qualified product inspection index range of the 3D printing concrete of the present invention is: water addition rate <8%; fluidity is 160-220mm; setting time is ≤90min; extrudability is good (continuous and uniform, no blockage, no fine cracks); support is good (the shape remains stable and does not collapse after extrusion); printing strength reduction rate is ≤20%; interlayer splitting strength (C20-C60) is ≥3.5MPa; surface microcracks (7 days) are absent when observed with the naked eye.
[0099] Comparative Example 1 is based on Example 2, but the introduction of montmorillonite is cancelled and cement is increased accordingly. It can be seen that compared with Example 2, the mass percentage of cement + mineral powder in Comparative Example 1 is too high, the water addition rate is too large, the extrudability, printing strength reduction rate, and interlaminar splitting strength performance are reduced, and a small amount of microcracks are observed on the surface after 7 days. The test result is unqualified. The test effect of Comparative Example 1 is significantly lower than that of Example 2.
[0100] Comparative Example 2 is based on Example 3, but the introduction of the composite anti-cracking agent is cancelled and cement is increased accordingly. It can be seen that compared with Example 3, the printing strength reduction rate and interlayer splitting strength performance of Comparative Example 2 are significantly reduced. After 7 days, many microcracks are observed on the surface, and the test results are unqualified. The test effect of Comparative Example 2 is significantly lower than that of Example 3.
[0101] Comparative Example 3 is based on Example 4, but the introduction of composite fibers is cancelled and cement is increased accordingly. It can be seen that compared with Example 4, the printing strength reduction rate and interlaminar splitting strength performance of Comparative Example 3 are significantly reduced. After 7 days, some microcracks are observed on the surface, and the test results are unqualified. The test effect of Comparative Example 3 is significantly lower than that of Example 4.
[0102] Comparative Example 4 is based on Example 5, but the introduction of the active agent is cancelled and the mineral powder is increased accordingly. It can be seen that compared with Example 5, the mass percentage of the active agent + citric acid in Comparative Example 4 is too low, the water addition rate is too large, the coagulation time is too long, the support is poor (the shape is unstable and easy to collapse after extrusion), the printing strength reduction rate and the interlayer splitting strength performance are significantly reduced, and many microcracks are observed on the surface after 7 days. The test results are unqualified. The test effect of Comparative Example 4 is significantly lower than that of Example 5.
[0103] Comparative Example 5 is based on Example 6, but the introduction of citric acid is cancelled and cement is increased accordingly. It can be seen that compared with Example 6, the setting time of Comparative Example 5 is too short (only 27 minutes, which is difficult to meet the requirements of on-site construction), the extrudability is general, the printing strength reduction rate and the interlayer splitting strength performance are slightly reduced, and a small amount of microcracks are observed on the surface after 7 days. The test result is unqualified. The test effect of Comparative Example 5 is significantly lower than that of Example 6.
[0104] In summary, the present invention aims at the surface cracks and subsequent penetration and cracking problems caused by excessive water addition in 3D printing concrete technology, and proposes an anti-cracking 3D printing concrete, which is composed of raw materials cement, 2-4mm steel slag, 0-2mm steel slag, mineral powder, secondary fly ash, bottom slag fine aggregate, montmorillonite, silica fume, composite anti-cracking agent, composite fiber, sodium silicate, active agent and citric acid. Through the design of each raw material component and ratio, moisture control is optimized, cracks are reduced, and structural strength and stability are enhanced, construction performance and fluidity are improved, and durability and waterproofness are improved. The development and application of the anti-cracking 3D printing concrete of the present invention can not only solve the core problems faced by the current 3D printing concrete field, but also lead the construction industry to a more efficient, environmentally friendly and intelligent future. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.
[0105] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A crack-proof 3D printed concrete, characterized in that: In terms of mass percentage, it includes the following raw material components: Cement 28-32%, 2-4mm steel slag 6-8%, 0-2mm steel slag 36-39%, mineral powder 7-10%, secondary fly ash 6-8%, bottom slag fine aggregate 5-7%, montmorillonite 2-3%, silica fume 0.5-1%, composite anti-cracking agent 0.5-1%, composite fiber 0.03-0.06%, sodium silicate 0.5-1%, activator 0.04-0.06%, citric acid 0.03-0.05%.
2. The anti-cracking 3D printing concrete according to claim 1, characterized in that: In terms of mass percentage, it includes the following raw material components: Cement 30%, 2-4mm steel slag 7%, 0-2mm steel slag 37%, mineral powder 8%, secondary fly ash 7%, bottom slag fine aggregate 6%, montmorillonite 2.5%, silica fume 0.8%, composite anti-cracking agent 0.86%, composite fiber 0.05%, sodium silicate 0.7%, activator 0.05%, citric acid 0.04%.
3. The anti-cracking 3D printing concrete according to claim 1, characterized in that: The cement is SAC 42.5 grade; And / or, the CaO content in the 2-4 mm steel slag is less than 3%; And / or, the CaO content in the 0-2 mm steel slag is less than 3%.
4. The anti-cracking 3D printing concrete according to claim 1, characterized in that: The mineral powder is of S95 grade; And / or, the particle size of the secondary fly ash is 325 mesh; And / or, the bottom slag fine aggregate particle size is 0 to 2 mm; And / or, SiO2 in the silica ash is ≥92%.
5. The anti-cracking 3D printing concrete according to claim 1, characterized in that: The sodium silicate and citric acid are both industrial grade; And / or, the montmorillonite contains A2O3≥46%, SiO2≥52%, and the particle size of the montmorillonite is 1250 mesh; And / or, the active agent is FS-65 type water reducing agent.
6. The anti-cracking 3D printing concrete according to claim 1, characterized in that: The composite anti-cracking agent has the following raw material components in percentage by weight: 20-30% CaSO4 whiskers and 70-80% light calcium carbonate; And / or, the raw material components of the composite fiber have the following weight percentages: 60-70% of chopped glass fiber and 30-40% of low melting point organic fiber.
7. The anti-cracking 3D printing concrete according to claim 1, characterized in that: The mass percentage of 0-2 mm steel slag + bottom slag fine aggregate in the 3D printing concrete is 42-45%.
8. The anti-cracking 3D printing concrete according to claim 1, characterized in that: The mass percentage of cement + mineral powder in the 3D printing concrete is 36.5-39.5%.
9. The anti-cracking 3D printing concrete according to claim 1, characterized in that: The mass percentage of the active agent + citric acid in the 3D printing concrete is 0.08-0.1%.
10. A method for preparing crack-resistant 3D printing concrete according to any one of claims 1 to 8, characterized in that: The steps include: S1. Premixing the composite anti-cracking agent, composite fiber, sodium silicate, active agent and citric acid to obtain a premixed small material; S2. Mix cement, 2-4 mm steel slag, 0-2 mm steel slag, mineral powder, secondary fly ash, bottom slag fine aggregate, montmorillonite, silica fume and water, add premixed small materials and continue to mix and stir evenly to obtain anti-cracking 3D printing concrete.
Citation Information
Patent Citations
Hybrid fiber cement-based composite material for 3D printing and preparation method thereof
CN109384437A
3D printing thermal insulation mortar and preparation method and application thereof
CN111517715A
Steel slag synergistic furnace bottom slag 3D printing concrete
CN117263627A